Non-linear Relationship Between Plasma Amyloid-β 40 Level and Cognitive Decline in a Cognitively Normal Population - Gao, Fan; Shang, Suhang; Chen, Chen; Dang, Liangjun; Gao, Ling; Wei, Shan; Wang, Jin; Huo, Kang; Deng, Meiying; Wang, Jingyi; Qu, Qiumin (Frontiers in Aging Neuroscience, 2020)
Objectives: Recent studies regarding the relationships between plasma amyloid-β (Aβ) levels and cognitive performance had inconsistent results. In this study, we aimed to characterize the relationship between cognitive decline and plasma Aβ levels in a large-sample cognitively normal population. Methods: This population-based, prospective cohort study included 1,240 participants with normal cognition. The Mini-Mental State Examination (MMSE) was used to assess cognitive function at baseline and two years later. Restricted cubic splines, multivariate logistic regression, and multivariate linear regression models were used to evaluate the type of relationship between cognitive decline during the 2-year follow-up period and plasma Aβ levels (Aβ40, Aβ42 and Aβ42/40). Results: Participants with moderate Aβ40 levels had the highest risk of cognitive decline during a 2-year follow-up relative to individuals with low Aβ40 (odds ratio [OR]: 0.60, 95% confidence interval [CI]: 0.45-0.81, p<0.001) or high Aβ40 (OR: 0.65, 95% CI: 0.49-0.87, p=0.004) levels. The association between Aβ40 and cognitive decline did not depend on sex, education level, or APOE ε4 status. There was an interaction found between age (≤65 and >65 years) and Aβ40 (p for interaction=0.021). In individuals older than 65 years, there was a positive linear relationship between plasma Aβ40 and cognitive decline (OR: 1.02, 95%CI: 1.00-1.04, p=0.027). For participants ≤65 years old, the lower Aβ40 and higher Aβ40 groups had a lower risk of cognitive decline than the medium Aβ40 group (OR: 0.69, 95% CI: 0.50-0.94, p=0.02; OR: 0.63, 95% CI: 0.45-0.86, p=0.004). None of relationship between plasma Aβ42, Aβ42/40 and cognitive decline was found during a 2-year follow-up. Conclusions: The relationship between plasma Aβ40 and cognitive decline was not linear, but an inverted-U shape in a cognitively normal population. The underlying mechanism requires further investigation.